Pengembangan Instrumen Tes Diagnostik Five-Tier untuk Identifikasi Miskonsepsi Siswa pada Materi Asam Basa, Hidrolisis Garam, dan Larutan Penyangga di SMAN 1 Likupang - Bawala, Nurmala S.; Rampe, Meytij J.; Tuerah, Jeanne Maria (General Chemistry Journal, 2025)
The purpose of this research is to determine the feasibility of the Five Level Diagnostic Test Instrument, especially on acid-base material, salt hydrolysis and buffer solutions to identify students’ misconceptions about this material. This research was conducted at SMAN 1 Likupang on class XI MIA 1 and XI MIA II students totaling 70 students. This research method uses the R&D method with the PLOMP model. The results of the validation of the questions by experts obtained a CVI value = 0.99 with the criteria "very suitable". Construct Validity with a person reliability value of 0.83 in the good category, item reliability of 0.77 sufficient criteria and person separation reliability of 3.35 good criteria and sufficient person separation criteria of 2.75. The results of reliability, distinguishing power and level of difficulty show good results. And the results of applying the instrument to each question show the highest student misconception profile in questions number 3, 6 and 8 with a percentage of 70% and the lowest misconception in question number 19 with a percentage of 16.66%. The subconcept that experienced the highest misconception was the theory of acids and bases and the strength of acids and bases, while the lowest subconcept was the concept of buffer solutions and the properties of buffer solutions.